Producing reliable hydrologic scenarios from raw climate model outputs without resorting to meteorological observations - Ricard, Simon; Lucas-Picher, Philippe; Thiboult, Antoine; Anctil, François (Hydrology and Earth System Sciences, 2023)
Abstract. A simplified hydroclimatic modelling workflow is proposed to quantify the impact of climate change on water discharge without resorting to meteorological observations. This alternative approach is designed by combining asynchronous hydroclimatic modelling and quantile perturbation applied to streamflow observations. Calibration is run by forcing hydrologic models with raw climate model outputs using an objective function that excludes the day-to-day temporal correlation between simulated and observed hydrographs. The resulting hydrologic scenarios provide useful and reliable information considering that they (1) preserve trends and physical consistency between simulated climate variables, (2) are implemented from a modelling cascade despite observation scarcity, and (3) support the participation of end-users in producing and interpreting climate change impacts on water resources. The proposed modelling workflow is implemented over four sub-catchments of the Chaudière River, Canada, using nine North American Coordinated Regional Climate Downscaling Experiment (NA-CORDEX) simulations and a pool of lumped conceptual hydrologic models. Results confirm that the proposed workflow produces equivalent projections of the seasonal mean flows in comparison to a conventional hydroclimatic modelling approach. They also highlight the sensibility of the proposed workflow to strong biases affecting raw climate model outputs, frequently causing outlying projections of the hydrologic regime. Inappropriate forcing climate simulations were however successfully identified (and excluded) using the performance of the simulated hydrologic response as a ranking criterion. Results finally suggest that further works should be conducted to confirm the reliability of the proposed workflow to assess the impact of climate change on high- and low-flow events.

What added value of CNRM-AROME convection-permitting regional climate model compared to CNRM-ALADIN regional climate model for urban climate studies ? Evaluation over Paris area (France) - Lemonsu, A.; Caillaud, C.; Alias, A.; Riette, S.; Seity, Y.; Le Roy, B.; Michau, Y.; Lucas-Picher, P. (Climate Dynamics, 2023)

Evaluation of the Urban Heat Island of 12 cities of France in a high-resolution regional climate model simulation - Michau, Y.; Lemonsu, A.; Lucas-Picher, P.; Caillaud, C. (Urban Climate, 2023)